Changing of antioxidant and sugar contents of self brewed beers during the brewing steps - Tóth-Szabó, Edina; Bora, Lilla; Sipos, Péter (Acta Agraria Debreceniensis, 2016)
Beer is a valuable beverage, its composition is influenced by raw materials and technology. We tried to determine how the technological steps influence the antioxidant content, the colur value, and the carbohydrate content, and how fruit syrups influence the antioxidant content and the colour value.